Keputusan Pembelian dan Kepuasan Konsumen Dipengaruhi Variabel Lokasi, Pelayanan, Kualitas Produk, Nilai Emosional, dan Disain Interior yang Berdampak pada Tingkat Pembelian - Bahri Bahri (Universitas Proklamasi 45 Yogyakarta, 2018)
This research is motivated by the growing of online businesses that have an impact on decreasing income of retail businesses. In order to survive, a retail business have to implement strategies that can increase purchases and provide satisfaction to consumers. This study aims to determine the effect of location, service, product quality, emotional value, and interior design variables on purchasing decisions and also customer satisfaction for increasing purchases, and testing the effect of purchasing decisions on customer satisfaction at Gardena Department Store & Supermarket. This type of research uses quantitative descriptive. The sampling method is non-probability sampling and using purposive sampling technique. The data that have been collected then analyzed using the statistical hypotheses test method consist of multiple linear regression analysis, t-test, and f-test. The partial results of the study indicate that the location, service, and product quality variables have positive and significant effects on purchasing decisions and customer satisfaction. While the emotional value and interior design variables have no partial effects on purchasing decisions and consumer satisfaction. Purchasing decisions has a significant positive effect on customer satisfaction. Simultaneously, the variables of location, service, product quality, emotional value, and interior design have positive and significant effects on purchasing decisions and customer satisfaction at Gardena Department Store & Supermarket. The results of this study can be used as an implication for company management that should continue to improve service, product quality, and need to pay attention to location, especially access and large parking lots so that consumers decide to make purchases and get satisfaction from the products, resulting an increase in consumer purchases at Gardena Department Store & Supermarket.